Can neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and mean platelet volume be used as inflammation markers in patient selection for tonsillotomy? - Başal, Yeşim; Kurt Ömürlü, İmran and Uysal, Pınar and Eryılmaz, Aylin and Başak, Sema (ENT Updates, 2016)
Objective: The aim of this study was to investigate whether mean platelet volume (MPV), neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) can be used as inflammation markers in selection of pediatric patients, who were planned to undergo tonsillotomy for sleep apnea, or not. Methods: The tonsillotomy group consisted of pediatric patients who had undergone tonsillotomy for sleep apnea between 2013–2015 years. The control group consisted of children who had presented to the WellChild Outpatient Clinics. The patient charts were reviewed retrospectively. MPV, NLR and PLR values were recorded and analyzed. Results: In the tonsillotomy group, there were 23 patients whereas the control group consisted of 31 healthy children. The median age was 5 in the tonsillotomy group and 6 in the control group. MPV, NLR and PLR values did not have statistically significant differences between the tonsillectomy and control groups (p=0.838, p=0.314 and p=0.896, respectively). Conclusion: MPV, NLR and PLR values are not inflammation markers that can be used in selection of patients to undergo tonsillotomy for sleep apnea.